2004
DOI: 10.1061/(asce)1084-0699(2004)9:5(360)
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Precipitation, Streamflow, and Evapotranspiration in the Great Plains of the United States

Abstract: Planning and strategic management of water resources are contingent on trends in water availability. In this study, the impact of decade-scale variations in annual and seasonal precipitation on streamflow and evapotranspiration ͑ET͒ were identified for 10 watersheds in Nebraska, Kansas, and Oklahoma. In the Great Plains, an upward trend in precipitation over the last two decades of the 20th Century had a strong impact on streamflow and a comparatively weaker impact on ET. Even though precipitation, streamflow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 15 publications
5
73
0
Order By: Relevance
“…While our study is focused on a single basin, the watershed exhibits similar hydrologic behavior to other regions in the Great Plains (Garbretch et al, 2004). As a result, basin response characteristics identified in this study may be applicable to similar settings in the broader region.…”
Section: Discussionmentioning
confidence: 90%
“…While our study is focused on a single basin, the watershed exhibits similar hydrologic behavior to other regions in the Great Plains (Garbretch et al, 2004). As a result, basin response characteristics identified in this study may be applicable to similar settings in the broader region.…”
Section: Discussionmentioning
confidence: 90%
“…Based on data for 1960-2011, Norton et al (2014) indicated a slightly increasing trend for the mean of the total annual precipitation in the Missouri River Basin. Garbrecht et al (2004) studied two watersheds in Nebraska and showed an increase in precipitation in both watersheds based on data for 1895-2001. Rahmani et al (2015) indicated an increasing trend in precipitation for the majority of Kansas using data from 1890 to 2011.…”
Section: Trends In Baseflow and Precipitationmentioning
confidence: 99%
“…Research was conducted to detect climate changes, trends and variability in various parts of the world utilizing some climate parameters such as air temperature, rainfall depth, reference evapotranspiration ET o and pan evapotranspiration ET p (Schwartz and Randall, 2003;Garbrecht et al, 2004;Hegerl et al, 2007;Fu et al, 2009;Saghravani et al, 2009;Hakan et al, 2010). ET o is of particular importance because it combine changes in many other climate parameters including temperature, radiation, humidity and wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, direct influence on hydrologic water balance, irrigation and drainage canal design, reservoir operation, potentials for rain-fed agricultural production and crop water requirements (Dinpashoh, 2006). Several studies conducted in North America have shown that some climate parameters are on the rise including ET o (Fehrman, 2007;Garbrecht et al, 2004;Szilagyi, 2001). Fehrman (2007) found an increasing trend in ET o over the Mississippi area and that most of ET o increase can be attributed to the increase in July.…”
Section: Introductionmentioning
confidence: 99%